Actualización en liquen plano oral (2000)
ABSTRACT: Licben planus (LP) is a relatively common disorder of the stratilied squamous epithelia. Lesions may affect other mucosae and/or skin. Orallichen planus (OLP) usually has a characteristic morphology and distribution, but OLP may also present a conlusing array of pattern and forms and other disorders may clinically simulate OLP Lichen planus is probably of multifactorial origin, sometimes induced for drugs or dental materials, often idiopathic, and with an immunopathogenesis involving T cells in particular. The etiopathogenesis appears to be complex, with interactions between and among genetic, environmental, and lilestyle Iectors, but much has now been cleritied about the mechanisms in volved, and interesting new associations with other diseeses, have emerged. The management 01 LP is stiJl not satisfactory, and there is as yet no definitive treatment, but there have been advances in the control 01 the condition. There is not curative treatment available, immunomodulation, however, can control the condition. Classical/y, it has been considered as premalignant entity, but recent researches suggest that there is a condition known as lichenoid dysplasia that requires ditterenciel diagnostic with LP ft is necessary more research into the genetic and environmental espects, its malignant potential, associations with other disorders and more clinical studies about therapy.